2015
DOI: 10.14393/bj-v31n2a2015-23571
|View full text |Cite
|
Sign up to set email alerts
|

Vascular epiphytes in a remnant of seasonal semideciduous forest in zona da mata of Minas Gerais, Brazil

Abstract: ABSTRACT:This study was performed in a remnant of Seasonal Semideciduous Forest at Fazenda Fortaleza de Sant'Anna, in the municipality of Chácara, Minas Gerais, Brazil (22.0129S, 43.8628W), in an area of ca. 1 ha, via monthly expeditions throughout the year 2012. We found 91 species of vascular epiphytes, distributed in 44 genera and 12 families. The richest families were Orchidaceae (35 spp.), Bromeliaceae (18 spp.), Polypodiaceae (10 spp.), Piperaceae (nine spp.) and Araceae (seven spp.). Two species were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…2). These are the three richest families in vascular epiphytes (Zotz 2013) in the Tropical Region (Gentry & Dodson 1989) and in the Atlantic Forest (Freitas et al 2016), and repeat a common pattern often found in local studies in Brazil in different physiognomies (e.g., Borgo & Silva 2003;Buzzato et al 2008;Mania & Monteiro 2010;Bonnet et al 2013;Alves & Menini Neto 2014;Barbosa et al 2015;Couto et al 2016;Furtado & Menini Neto 2016;Joanitti et al 2017). It is worth mentioning the fact that SM concentrates 23 of the 33 families with epiphytic representatives found in the Atlantic Forest (Freitas et al 2016) or approximately 1/3 of those Rodriguésia 73: e01712020.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…2). These are the three richest families in vascular epiphytes (Zotz 2013) in the Tropical Region (Gentry & Dodson 1989) and in the Atlantic Forest (Freitas et al 2016), and repeat a common pattern often found in local studies in Brazil in different physiognomies (e.g., Borgo & Silva 2003;Buzzato et al 2008;Mania & Monteiro 2010;Bonnet et al 2013;Alves & Menini Neto 2014;Barbosa et al 2015;Couto et al 2016;Furtado & Menini Neto 2016;Joanitti et al 2017). It is worth mentioning the fact that SM concentrates 23 of the 33 families with epiphytic representatives found in the Atlantic Forest (Freitas et al 2016) or approximately 1/3 of those Rodriguésia 73: e01712020.…”
Section: Resultsmentioning
confidence: 65%
“…This remarkable presence of epiphytes in the tropical cloud forests (Hamilton et al 1995;Bruijnzeel et al 2010), their ecological importance, and issues related to conservation (Benzing 1990;Zotz 2016) are responsible for several questions and highlight the necessity to better understand the diversity and distribution of this sinusya species. Thus, several recent studies have been published regarding the vascular epiphytes occurring in the SM, with part of them concentrated in the cloud forests, reinforcing its diversity (Menini Neto et al 2009a;Barbosa et al 2015Barbosa et al , 2020Alves & Menini Neto 2014;Furtado & Menini Neto 2015, 2018a. It is worth mentioning the checklist for the Parque Estadual do Ibitipoca in Minas Gerais state (Furtado & Menini Neto 2018a) as one of the richest published in Brazil, recording 224 species distributed in approximately 300ha of cloud forests.…”
Section: Introductionmentioning
confidence: 97%